2012
DOI: 10.1007/s10616-012-9463-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of Oroxylum indicum bark extracts: antioxidant, antimicrobial, cytotoxic and apoptotic study

Abstract: Stem bark of Oroxylum indicum (L) (SBOI) is used by ethnic communities of North East India as health tonic and in treating diseases of humans and animals. The objective of this research was to carry out a detailed investigation including total phenolic and flavonoid content, antioxidant, antimicrobial, cytotoxic and apoptotic activities of different solvent extracts of SBOI and to establish correlation between some parameters. Among petroleum ether (PE), dichloromethane and methanol (MeOH) extract of SBOI, MeO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 29 publications
3
19
1
Order By: Relevance
“…The cytotoxicity of plant extracts with LC 50 value ≤ 20 µg/mL was regarded as a possible cytotoxic plant extract [63]. The results indicated that most plant extracts had low cytotoxicities with considerably high LC 50 value ≥ 100 µg/mL, excluding S. tuberculate (LC 50 = 25.9 µg/mL), D. odorifera (LC 50 = 44.1 µg/mL), I. japonica (LC 50 = 54.1 µg/mL), R. chinensis (LC 50 = 77.6 µg/mL), and Q. infectoria (LC 50 = 91.6 µg/mL), supporting by previous studies that also found a weak cytotoxicity of T. chebula [64,65], S. suberectus [66], Q. infectoria [67,68] and O. indicum [37]. However, it is necessary to test the toxicity by in vivo studies, since in vitro cellular toxicity might provoke different consequences in animals associated with gut interactions and bioavailability of the extracts [18].…”
Section: Cytotoxicity and Safety Of The Tcmp Extractssupporting
confidence: 83%
See 1 more Smart Citation
“…The cytotoxicity of plant extracts with LC 50 value ≤ 20 µg/mL was regarded as a possible cytotoxic plant extract [63]. The results indicated that most plant extracts had low cytotoxicities with considerably high LC 50 value ≥ 100 µg/mL, excluding S. tuberculate (LC 50 = 25.9 µg/mL), D. odorifera (LC 50 = 44.1 µg/mL), I. japonica (LC 50 = 54.1 µg/mL), R. chinensis (LC 50 = 77.6 µg/mL), and Q. infectoria (LC 50 = 91.6 µg/mL), supporting by previous studies that also found a weak cytotoxicity of T. chebula [64,65], S. suberectus [66], Q. infectoria [67,68] and O. indicum [37]. However, it is necessary to test the toxicity by in vivo studies, since in vitro cellular toxicity might provoke different consequences in animals associated with gut interactions and bioavailability of the extracts [18].…”
Section: Cytotoxicity and Safety Of The Tcmp Extractssupporting
confidence: 83%
“…Of the TCMP extracts evaluated, multidrug-resistant S. aureus strains were impacted with a high degree of susceptibilities, expressed as MIC, to R. chinensis (0.1-0.195 mg/mL), followed by Q. infectoria (0.195 mg/mL), C. chinensis [36] reported that gall extract of R. chinensis was more effective against S. aureus (MIC = 0.25 mg/mL) among tested microorganisms. Moirangthem et al [37] found that the bark extract from O. indicum exhibited strong antibacterial effects against S. aureus (MIC = 62.5 µg/disc), and also showed a broad antibacterial spectrum against Gram-positive and Gram-negative bacteria with the MIC values ranging from 62.5 to 250 µg/disc. Similar to the results obtained in this study, Tayel et al [38] reported that the extract of Q. infectoria exhibited strong inhibitory effects against S. aureus with the MIC value for 0.313 mg/mL.…”
Section: Selected Tcmp Extracts With a Wide Range Of Antibacterial Acmentioning
confidence: 99%
“…The decrease in the level of TBARS after administration of AMBEOI in the liver tissue of APAP intoxicated rat suggested the strong antioxidant property present in the AMBEOI. Previously reported studies also confirmed the antioxidant property of the selected plant species under consideration (Moirangthem et al, 2013;Zaveri and Jain, 2007;Shetgiri et al, 2010;Tenpe et al, 2009). The observation that administration of AMBEOI reduces formation of TBARS and similar findings from other researchers confirmed that AMBEOI act as strong antioxidant and protects the hepatocytes during APAP overdose.…”
Section: Discussionsupporting
confidence: 62%
“…The plant selected for the present study is reported to possess strong antioxidant properties (Moirangthem et al, 2013). The decrease in the level of TBARS after administration of AMBEOI in the liver tissue of APAP intoxicated rat suggested the strong antioxidant property present in the AMBEOI.…”
Section: Discussionmentioning
confidence: 80%
“…In vitro antioxidant activity of n-butanol extract of stem and root bark of O. indicum was determined by 2, 2′-Azino-bis(3ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) radical cation decolorization assay and reveals the presence of very high significant antioxidant activity . In vitro antioxidant activity (IC 50 22.7 μg/ml) was the highest in methanolic extract of stem bark of O. indicum (Moirangthem et al, 2013). The ethanol extract of stem bark exhibited maximum antioxidant potential due to its free radical scavenging activities in b-carotene bleaching assays, whereas chloroform extract showed maximum reducing power in total antioxidant activity may be due to its reducing potential (Kalaivani and Mathew, 2009).…”
Section: Antioxidant Activitymentioning
confidence: 99%